2015
DOI: 10.1177/0030222815574834
|View full text |Cite
|
Sign up to set email alerts
|

Grief Experiences Among Female American and Arab Undergraduate College Students

Abstract: The purpose of this study was to compare the incidence of grief among American and Arab female undergraduate students, the effects of their grief, and risk of prolonged grief disorder. A total of 471 female undergraduate students, 308 (65.4%) from the United Arab Emirates and 163 (34.6%) from the United States, completed a survey about their grief experiences. Students experiencing a significant loss also completed the Prolonged Grief Disorder Questionnaire. Findings revealed that overall approximately 38.4% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…Indeed, Lundorff et al ( 1 ) even showed that the PG-13 used in our study was associated with lower PGD rates (3.2%) compared to other diagnostic tools. Moreover, the prevalence in the present sample is also higher than that reported in other Arabic-speaking samples [15.1% in refugees in a camp in Jordan, ( 7 ); 12% in bereaved Saudi Arabian undergraduate students, ( 5 ); 5% in female university students in the United Arab Emirates, ( 6 )]. This discrepancy might be explained by the fact that our sample was treatment-seeking, meaning that the participants were already aware of their mental health problems and thus actively seeking help, albeit not specifically for PGD.…”
Section: Discussioncontrasting
confidence: 73%
“…Indeed, Lundorff et al ( 1 ) even showed that the PG-13 used in our study was associated with lower PGD rates (3.2%) compared to other diagnostic tools. Moreover, the prevalence in the present sample is also higher than that reported in other Arabic-speaking samples [15.1% in refugees in a camp in Jordan, ( 7 ); 12% in bereaved Saudi Arabian undergraduate students, ( 5 ); 5% in female university students in the United Arab Emirates, ( 6 )]. This discrepancy might be explained by the fact that our sample was treatment-seeking, meaning that the participants were already aware of their mental health problems and thus actively seeking help, albeit not specifically for PGD.…”
Section: Discussioncontrasting
confidence: 73%
“…Regarding gender, women comprised the majority of study participants, as an average of 62.1% was female. Single study mean age ranged from 21 (Varga et al, 2015) to 74.5 years (Byrne and Raphael, 1994) and the overall mean age was 52.2 years (SD=15.2). Participants' relation to the deceased varied with the most common types of losses being spousal (34.72%) and parental (27.65%) bereavement.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Six studies scored 7 or 8 points (Fujisawa et al, 2010;He et al, 2014;Kim et al, 2015;Li and Prigerson, 2016;O'Connor et al, 2010;Prigerson et al, 2009), which corresponds to a moderate RoB. The remaining four studies scored 6 or less points (Byrne and Raphael, 1994;Goldsmith et al, 2008;Middleton et al, 1996;Varga et al, 2015) and were consequently labelled as high RoB. The studies' RoB scores ranged from 5 to 10 out of 10 possible points (M=7.5, SD=1.5).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…In addition, Varga, McClam, and Hassane (2015) identifi ed grief experiences among American and Arab female undergraduate students to compare the incidence of grief, the effects of grief, and risk of PGD. In total, 471 students (308 [65.4%] from the United Arab Emirates and 163 [34.6%] from the United States) completed a survey relating to their grief experiences.…”
Section: Prolonged Grief Disorder Among University Studentsmentioning
confidence: 99%
“…Female students in the current study had higher PGD scores than their male counterparts, but no clear reason for this difference was seen. Given the differences in grief effects between female American and Arab students found by Varga et al (2015), it may be that cultural issues are at play, particularly in a country such as Saudi Arabia, which is characterized by a male-dominated society. This fi nding will require additional investigation.…”
Section: Unclear Picture Of Gender Diff Erencesmentioning
confidence: 99%